The influence of locus of control, work stress and work conflict on the performance of Bank Indonesia employees in West Sumatra - Didi Aryadi; M. Iqbal Pahlawi (Jurnal Mantik, 2023)
Employee performance is the result of work produced by an employee based on the duties and responsibilities given by the organisation. The achievement of employee performance has an impact on the achievement of organisational goals. An employee is required to produce good performance, so that the company is able to achieve its goals. Employee performance can be influenced by individual factors, among others, in the form of psychological characteristics, namely locus of control, which is an aspect of personality that refers to an individual's psychological system and unique traits that can decide how a person thinks and behaves. This study aims to determine the effect of locus of control, work stress and work conflict on the performance of Bank Indonesia West Sumatra employees. The method used in this research is quantitative research with a descriptive approach. The population in this study were all employees of Bank Indonesia West Sumatra. The sample used was 68 people using the total sampling method. The data analysis technique is multiple linear regression. The results of the study show that: (1) Locus of control has a positive and significant effect on the performance of Bank Indonesia West Sumatra employees. (2) Work stress has a positive and significant effect on the performance of West Sumatra Bank Indonesia employees. (3) Work conflict has a negative and significant effect on the performance of Bank Indonesia West Sumatra employees. (4) Locus of control, work stress and work conflict simultaneously have a significant effect on the performance of Bank Indonesia West Sumatra employees.